Stroke and lipid profile in a cardiovascular risk program of Armenia, Quindío (Revista de Investigaciones Universidad del Quindío, 2022)
Objective: To describe the lipid profile in patients with stroke in a cardiovascular risk program in a first-level health institution in Armenia, Quindío during 2018.Methods: A cross-sectional descriptive study was carried out with a sample of 300 people in a population of a first-level service provider institution with diagnosis or history of stroke. Variables were described in average, standard deviation and confidence intervals, a comparative analysis was made by sex. Variance analysis and square Chi were performed. A relationship of the lipid profile variables with the diagnosis and history of stroke was established. A value of p
Keywords: Stroke; Cholesterol; Cholesterol-HDL; Triglycerides